Ethic problems of public health service - A. S. Chernov; S. A. Soloviyova; Ye. M. Borzunova (Бюллетень сибирской медицины, 2006)
The paper is devoted to ethic problems of public health service during second-generation epidemiological AIDS inspections. The necessity of ethic expertise of any AIDS investigation is justified. The experience of organization of an ethic committee in the USA in a health care facility is described.